Accelerated‐curing epoxy structural film adhesive for bonding lightweight honeycomb sandwich structures. Issue 6 (29th November 2022) - Zhao, Liwei; Li, Hongfeng; Qiao, Yingjie; Bai, Xuefeng; Wang, Dezhi; Qu, Chunyan; Xiao, Wanbao; Liu, Ye; Zhang, Jian
Abstract: Accelerating the curing of epoxy/aromatic amine adhesives and improving their toughness are challenges in heat‐resistant epoxy structural adhesives. Herein, we report an epoxy/aromatic amine adhesive accelerated curing system with an oxo‐centered trinuclear (chromium III) complex, which is toughened using a thermoplastic block copolymer (TPBC). The reaction characteristics, heat resistance, microstructure, and bonding properties of the accelerated epoxy adhesives were analyzed. The reaction peak temperature of the epoxy with 3% catalyst was 113.1°C, which was 113.6°C lower than that of epoxy without catalyst, and the modified epoxy resin demonstrated a potential for rapid curing at medium temperature. The glass transition temperature of the TPBC‐toughened epoxy adhesive was 125°C after curing, indicating excellent thermal stability after medium temperature curing. The introduction of the TPBC increased the single‐lap shear strength of the epoxy adhesive without reducing its heat resistance. The shear strength at room temperature and 120°C of the modified epoxy adhesive with 50 phr of TPBC was 25.2 and 10.9 MPa, respectively. Moreover, the epoxy film adhesive exhibited outstanding bonding properties when used in the bonding of lightweight honeycomb sandwich structures. Abstract : An accelerated curing epoxy/aromatic amine adhesive system with oxo‐centered trinuclear (chromium III) complex is designed, and then toughened using a thermoplastic block copolymer. The epoxy film adhesive can be cured at lower temperatures and exhibits excellent heat resistance and bonding properties. Thus, the film adhesive exhibits outstanding bonding properties when used in the bonding of lightweight honeycomb sandwich structures.